2011
DOI: 10.1161/circresaha.110.229393
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Calpain in the Endothelial Dysfunction Induced by Activation of Angiotensin II Type 1 Receptor Signaling

Abstract: Rationale The cytosolic protease calpain has been recently implicated in the vascular remodeling of angiotensin II (AngII) type-1 receptor (AT1r) signaling. The role of AngII/AT1r/calpain signaling on endothelial function, an important and early determinant of vascular pathology, remains though totally unknown. Accordingly, we investigated the role of calpain in the endothelial dysfunction of AngII. Objective To demonstrate a mechanistic role for calpain in the endothelial dysfunction induced by AngII/AT1r s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 41 publications
3
34
0
1
Order By: Relevance
“…44 Other calpain inhibitors attenuate angiotensin II-induced abdominal aortic aneurysms and atherosclerosis in LDL receptordeficient mice 45 and angiotensin II-induced endothelial dysfunction in rats and mice. 46 The results of the present study, together with the studies showing a beneficial effect of calpain inhibition in vascular disease, highlight the potential of calpain inhibition for the treatment of the vascular complications of type 2 diabetes. However, future efforts should focus on the development of compounds devoid of the problems of calpain isoform selectivity and specificity versus other proteases, 47 which have hampered the progression of calpain inhibitors into clinical trials.…”
Section: Discussionsupporting
confidence: 57%
“…44 Other calpain inhibitors attenuate angiotensin II-induced abdominal aortic aneurysms and atherosclerosis in LDL receptordeficient mice 45 and angiotensin II-induced endothelial dysfunction in rats and mice. 46 The results of the present study, together with the studies showing a beneficial effect of calpain inhibition in vascular disease, highlight the potential of calpain inhibition for the treatment of the vascular complications of type 2 diabetes. However, future efforts should focus on the development of compounds devoid of the problems of calpain isoform selectivity and specificity versus other proteases, 47 which have hampered the progression of calpain inhibitors into clinical trials.…”
Section: Discussionsupporting
confidence: 57%
“…In cultured vascular smooth muscle cells, stimulation with angiotensin II (Ang II) has increased the calpain activity through transactivation of epidermal growth factor receptor and systemic overexpression of calpastatin blunted cardiac hypertro- phy and perivascular inflammation in Ang II-infused mice (53). A recent study showed that calpain activation mediated Ang II-induced endothelial dysfunction in rodents (54). It is intriguing that activation of Ang II receptor signaling by locally produced Ang II and mechanical stress (28) may lead to calpain activation and thereby promote LV remodeling after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrocellulose membranes were incubated with rabbit-polyclonal antibody anti-NCX3 (1: 3000; kindly provided by K. Philipson), or mouse monoclonal anti-NCX1 (1:500; Swant), or mouse monoclonal anti-tubulin (1:1000), or rabbit polyclonal antibodies anti-caspase-12 (1:1000) and goat polyclonal anti-calpain (1:500) (Santa Cruz Biotechnology). Calpain activation was assessed by immunoblot analysis using a primary antibody that recognizes the calpain large subunit domain, which is autolyzed in active calpain from the full length calpain at 130 kDa, as already reported (Goll et al, 2003;Scalia et al, 2011;Selimovic et al, 2011).…”
Section: Methodsmentioning
confidence: 99%